2021
DOI: 10.3390/ijms222212497
|View full text |Cite
|
Sign up to set email alerts
|

HBV HBx-Downregulated lncRNA LINC01010 Attenuates Cell Proliferation by Interacting with Vimentin

Abstract: Hepatitis B virus (HBV) infection is closely related to hepatocellular carcinoma (HCC) development. To investigate the mechanism of HBV causing HCC, we previously analyzed the transcription of the HBV-transgenic cell line HepG2-4D14 and parental HepG2 cells and identified a subset of long noncoding RNAs (lncRNAs) differentially expressed between them. In this study, we focus on lncRNA LINC01010, as it is significantly downregulated in HepG2-4D14 cells and in liver tissues of HCC patients, and positively correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…In most cases, HBV alters the non-coding RNA expression to elevate the expression levels of oncogenic genes, thus leading to the development of cancer. But several studies have reported the suppressive effect of non-coding RNAs on HCC development (Deng et al, 2020;Gan et al, 2021). Another mechanism of HBV infection-mediated repression of the development of HCC is by reducing the expression of miR-15a and miR-16-1.…”
Section: Non-coding Rnas Suppress the Progression Of Hepatitis B Viru...mentioning
confidence: 99%
“…In most cases, HBV alters the non-coding RNA expression to elevate the expression levels of oncogenic genes, thus leading to the development of cancer. But several studies have reported the suppressive effect of non-coding RNAs on HCC development (Deng et al, 2020;Gan et al, 2021). Another mechanism of HBV infection-mediated repression of the development of HCC is by reducing the expression of miR-15a and miR-16-1.…”
Section: Non-coding Rnas Suppress the Progression Of Hepatitis B Viru...mentioning
confidence: 99%
“…115 4.7 | Long intergenic nonprotein coding RNA 1010 (LINC01010) LINC01010 is a transcript recently noted to be downregulated in lung, breast, and liver cancers. [116][117][118] Several groups have analyzed and reported on the positive correlation between LINC01010 expression and more favorable prognostic outcomes in these cancers as well as neuroblastomas, leading to hypotheses that it may function as a tumor suppressor. [116][117][118][119] Considering that LINC01010 is expressed at significantly lower levels in patient tumor tissue relative to normal tissue in The Cancer Genome Atlas-Liver Hepatocellular Carcinoma (TCGA-LIHC) cohort, one group aimed to further dissect the correlations between HBV and LINC01010 expression.…”
Section: Plasmacytoma Variant Translocation 1 (Pvt1) Lncrnamentioning
confidence: 99%
“…Considering that LINC01010 is expressed at significantly lower levels in patient tumor tissue relative to normal tissue in The Cancer Genome Atlas–Liver Hepatocellular Carcinoma (TCGA‐LIHC) cohort, one group aimed to further dissect the correlations between HBV and LINC01010 expression. 63 HCC patient samples were classified as either “high” or “low” HBV‐load groups based on copies of HBV in patient sera, and RT‐qPCR data demonstrated significantly lower amounts of LINC01010 in the high HBV‐load group relative to the low HBV‐load group 118 . Subsequent experiments demonstrated lower LINC01010 levels in L02 cells transfected with pcDNA3.1‐HBV1.3, which contains a replication‐competent copy of the HBV genome, versus pcDNA3.1 alone, and a HepG2‐GFP‐HBx stable cell line relative to HepG2‐GFP.…”
Section: Lncrnas Dysregulated In Hbv Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LINC01010 interferes with vimentin polymerization and then inhibits the proliferation and migration ability of liver cancer cells. Thus, LINC01010 is a potential tumor suppressor that can inhibit HBV-related liver cancer development [ 12 ]. The lncRNA SAMD12-AS1 is a new cancer-promoting lncRNA, and its function is less studied.…”
Section: Introductionmentioning
confidence: 99%